Novel eco-friendly linear gel for oil well recovery through efficient hydrofracturing - R. V. V. Ramana Murthy; K. S. R. Murthy; Murthy Chavali (PT Mattawang Mediatama Solution, 2021)
The linear gel is prepared by treating bio-diesel with various water samples collected from different water bodies. The new biodiesel based linear gel was employed in the recovery of oil wells through hydrofracturing and pilot tests were conducted for the first time. The viscosity of gel was measured at various bottom hole-circulating temperatures and it was found to vary from 32 to zero dial reading in the range of 45ºC to 60ºC. The gel was observed to break at 45ºC and 60ºC in 120 min. So the final temperature was selected as 60ºC for the application of gel for coal bed methane (CBM) wells. It was observed that higher levels of salinity in water helped in optimum utilization of gel in real-time application.